On the existential core of professionalism in mental health care - Glas, G. (Mental health, religion & culture, 2017)
Existential issues are at the heart of professional role fulfilment. To defend this thesis, it will first be shown that professional competence not only consists of knowledge and skills, but also includes a second-order capacity which enables the clinician to dose and guide his activities. Secondly, in the way the professional performs his or her role, there is also always something communicated about how the professional relates to his or her role performance. This "indirect" communication is not an undesirable by-product of the communication with the patient, it is intrinsic to the professional role. Thirdly, the shaping of this "self-relatedness" can be conceptualised as the result of an interaction between basic (existential) motives in the professional and the normative appeal of the therapeutic setting. A conceptual model of the professional - patient relationship will be presented that clarifies the different dimensions and relations which are addressed in the three successive steps.